Diversity in Morphometric, Pomological, and Fruit-Quality Traits of Apricot (Prunus armeniaca) Traditional Varieties: Implications for Landrace Differentiation at Regional Scale - Boris Basile; Alessandro Mataffo; Marcello Forlani; Giandomenico Corrado (Diversity, 2022)
Traditional crop varieties are receiving increasing attention in sustainable agriculture, conservation genetics, and plant science because they offer significant and largely unexplored diversity. The DNA profiling of landraces is being applied to numerous crops, yet a detailed knowledge of morphological diversity is often needed to increase the efficiency of both the conservation and exploitation of local germplasm. In this work, morphological, pomological, and fruit-quality traits (16 qualitative and 16 quantitative) were collected from 44 traditional apricot landraces cultivated in Campania, the Italian region with the highest number of traditional varieties. The aim was to assess varietal diversity and to highlight possible trends and phenotypes that may have driven the morphological differentiation. All traits were polymorphic, and each variety had a distinctive phenotype. The qualitative and quantitative traits provided different classifications of the varieties. Nonetheless, the Factorial Analysis of Mixed data indicated that, for both categories of variables, the fruit traits were the most influential for landrace classification. Interestingly, some easily discernible color phenotypes of the fruits mostly contributed to the discrimination of the analyzed apricot germplasm. We conclude that these specific, commercially relevant features of the fruit were important drivers of the differentiation of the cultivated apricot material at regional scale.